Measuring time with high precision in particle physics. Issue 11 (2nd December 2022) - Kaynak, B.; Ozkorucuklu, S.; Penzo, A.
Abstract : Time measurements with sub-nanosecond time resolution (aiming at values of few picoseconds) are of paramount importance for a wide variety of applications. In the field of particle physics, measuring with increasing precision the time taken by a particle to travel between two points (Time-of-Flight, ToF) gives information on the particle' (relativistic) velocity, contributing to identifying the type of particle (Particle Identification Detectors, PID). Among this category of detectors are also Cherenkov counters, based on the emission of light when a charged particle travels in a transparent medium with a velocity exceeding the light velocity in that medium. Here we discuss a special category of ToF counters using the properties of Cherenkov light to determine the passage of the particles through the detectors with unprecedented precision. Results obtained with test beams are described and analysed, demonstrating the excellent timing resolution that can be obtained. Such detectors may be used to provide a 'precision time reference' for calibrating other types of timing detectors. Other applications are, for instance, time-tagging of 'pile-up' events in high-luminosity Large Hadron Collider (LHC), and identification of events with anomalous timing properties (for instance, long-lived particles, LLP).